استراتيجيات تعلم النَحو لدى دارسي اللغة العربية في الجامعة الإسلامية العالمية بماليزيا : دراسة وصفية تحليلية - Siti Aishah binti Muslim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study concerns the use of syntax learning strategies among non-native speakers majoring in Arabic language. It aims to investigate the level of the use of those strategies, the relationship between syntax learning strategies and students' academic achievement, as well as the significant difference between genders. A sample of 201 students from the Department of Arabic Language and Literature at the International Islamic University Malaysia (IIUM) was selected using convenience sampling method. The study adopted a questionnaire from Pawlak (2012) which consists of 24 items which assessed 3 parts of strategies: Implicit learning, explicit inductive and explicit deductive. The study revealed that the most frequent strategies used by students are the explicit inductive learning strategies, which confirms the strong relationship between teaching methods employed by teachers of Arabic syntax and learners' use of strategies. However, the study found no relationship between the use of syntax learning strategies and academic achievement, as well as no significant difference between gender in the use of these strategies, though female students employ more syntax learning strategies as compared to male. This study concludes with several practical recommendations to help Arabic students to be more successful in learning Arabic syntax.